Konsep Diri dan Pengungkapan Diri Laki-Laki dalam Multi Account Instagram - Miladia Arifa; Ratna Permata Sari (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
Male Instagram users are considered to have minimal self-concept and expression compared to women. This phenomenon is rarely studied. This research was conducted to determine the formation of self-concept and self-disclosure of men on multiple Instagram accounts. This study uses a qualitative method. Data was collected through in-depth interviews with five informants who were male and had more than one account. This study found that multiple accounts have several functions for their users. First accounts are more likely to be used to build a positive professional image. On the other hand, in the second account, the informant tried to appear more confident, comfortable and expressive. The informant's self-disclosure is also greater in the second account. This is because the second account involves the closest people who know the informant directly.